NP-guide: a portable projection-based navigation system for neurosurgery and beyond - Shi, Zhongjie; Gao, Xin; Chen, Sifang; Xiao, Deyong; Li, Zhangyu; Li, Xiaojun; Peng, Yilong; Yu, Jiajia; Wang, Zhanxiang (Frontiers in Neurology, 2025)
BackgroundStereotactic systems and various robot-assisted navigation platforms in neurosurgery have enabled high-precision localization. However, these systems, while highly accurate, are expensive, technically demanding, and procedurally complex, making them less practical for routine use. This study introduced and evaluated the Navigation and Projection Guide (NP-Guide), a projection-based augmented reality (AR) system designed to provide a portable and accessible solution for surgical navigation.MethodsNP-Guide, a mobile application, projects patient imaging data and three-dimensional (3D) reconstructions onto the patient’s head surface to assist with localization. This proof-of-concept study prospectively enrolled 52 neurosurgical patients, randomized to the NP-Guide group (n = 27) or the freehand localization group (n = 25). Two physicians with different training backgrounds performed the procedures. Localization error and operating time were measured using a commercial optical navigation system (ONS). Bland–Altman analysis was applied to assess inter-operator agreement, and learning curves were generated to evaluate proficiency.ResultsBaseline characteristics were comparable (all p > 0.05). In the NP-Guide group, mean localization error was 4.1 ± 2.1 mm for Physician A and 3.4 ± 1.8 mm for Physician B, with mean times of 1.2 ± 0.5 min and 1.1 ± 0.4 min, respectively. Compared with freehand localization, NP-Guide significantly improved the accuracy and efficiency (all p < 0.001). Bland–Altman analysis demonstrated good inter-operator agreement; no significant difference was observed (p = 0.25). Learning curves showed that operating times plateaued at approximately 1 min after about 15 cases.ConclusionThe NP-Guide demonstrated accurate, efficient, and reproducible projection-based localization in this proof-of-concept study. Its portability, low cost, and ease of use suggest potential value, particularly in resource-limited settings. However, these findings should be interpreted as preliminary, and further phantom experiments and multicenter clinical studies are required before widespread adoption in routine practice.